2022
DOI: 10.1371/journal.pone.0270053
|View full text |Cite
|
Sign up to set email alerts
|

Linear breakwater reefs of the greater Caribbean: Classification, distribution & morphology

Abstract: Geomorphic differences among Caribbean reefs have long been noted. These differences are considered to reflect the presence of reefs in different stages of development, following an incomplete recovery from rapid deglacial sea-level rise. But the possibility that these reflect real developmental differences caused by variation in wind, wave, and climate regime, has never been fully considered. Here, for the first time, we quantify the geomorphology and distribution of Greater Caribbean reefs using satellite im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Here, we found that the more simple metric of seamount shape, translating to only six categories, was sufficient to differentiate features in terms of their coral communities. Our recategorization of seamounts is similar to a concurrent parallel effort in shallow, linear breakwater reefs, which recently parsed 1023 breakwater reefs in the Caribbean into 16 reef subtypes only 9 of which were common (Blanchon et al, 2022).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Here, we found that the more simple metric of seamount shape, translating to only six categories, was sufficient to differentiate features in terms of their coral communities. Our recategorization of seamounts is similar to a concurrent parallel effort in shallow, linear breakwater reefs, which recently parsed 1023 breakwater reefs in the Caribbean into 16 reef subtypes only 9 of which were common (Blanchon et al, 2022).…”
Section: Discussionmentioning
confidence: 61%
“…Seamounts can form Taylor columns (Chapman & Haidvogel, 1992), localized upwelling and downwelling (White et al, 2007), internal waves to break resuspending sediment (Turnewitsch et al, 2013), tidal rectification (Brink, 1995;Mohn et al, 2009), and increased chlorophyll a concentrations (Leitner et al, 2020). Similarly, in shallow water coral reefs, it has recently been shown that variation in wind, wave, and climate regime have influenced the geomorphic development of different reef types (Blanchon et al, 2022). However, few studies have directly drawn the connection between these physical oceanographic changes (that are caused in part by the shape of the seamount) with the variation of their benthic communities; though seamounts are known to be hotspots of biodiversity (Rogers, 2018).…”
Section: Discussionmentioning
confidence: 99%